Perceived benefits and limitations of a psychoeducation program for patients with fibromyalgia: an interpretative phenomenological analysis - Di-Bonaventura, Silvia; Ferrer-Peña, Raúl; Pardo-Montero, Joaquín; Férnandez-Carnero, Josué; La Touche, Roy (Frontiers in psychology, 2024)
To analyze the perceived benefits and limitations of a pain psychoeducation program as a non-pharmacological treatment for patients with fibromyalgia. An interpretative phenomenological analysis was applied to analyze the subjective experiences of 11 patients with fibromyalgia who participated in a pain psychoeducation program. This program includes educational sessions that address pain understanding, coping strategies, and relaxation techniques. Semi-structured interviews were conducted, transcribed, and analyzed using ATLAS.ti software. Patients reported significant improvements in cognitive-functional capacity and socio-emotional ability, including better disease understanding and management, emotional stability, and interpersonal relationships. Despite these benefits, they identified limitations in program individualization and insufficient coverage of certain topics, such as sexual health and legal aspects of disability. Enhanced self-management skills were evident, with observed shifts in disease perception and coping strategies. The psychoeducation program was viewed positively, influencing functional, cognitive, and emotional enhancements. Nonetheless, the need for increased program personalization and expanded socio-economic support was noted. Future research should focus on the long-term impacts of psychoeducation and the feasibility of tailored interventions.